Topical effect of propolis in the repair of sulcoplasties by the modified Kazanjian technique. Cytological and clinical evaluation. - Magro-Filho, O.; de Carvalho, A. C. (Nihon University School of Dentistry, 1994)
A study was conducted to analyze the effects of propolis mouth rinse on the repair of surgical wounds after sulcoplasty by the modified Kazanjian technique. Twenty-seven patients who underwent sulcoplasty were divided into three groups: C1--patients who did not use the mouth rinse C2--patients who used a mouth rinse containing 5% aqueous alcohol T--patients who used a mouth rinse containing 5% propolis in aqueous alcohol solution. The patients returned 7, 14, 30, and 45 days after surgery for cytological and clinical evaluation. It was concluded that: 1) the mouth rinse containing propolis in aqueous alcohol solution aids repair of intra-buccal surgical wounds and exerts a small pain-killing and anti-inflammatory effect; 2) the vehicle employed has a minor irritant effect on intra-buccal surgical wounds; 3) exfoliative cytology allows epithelization of intrabuccal surgical wounds.
Keywords: antiinflammatory agent; propolis; clinical trial; controlled clinical trial; controlled study; drug effect; human; methodology; mouth hygiene; oral surgery; osteolysis; postoperative complication; wound healing; Alveolar Bone Loss; Anti-Inflammatory Agents; Humans; Mouthwashes; Postoperative Complications; Propolis; Vestibuloplasty; Wound Healing